The Development of Islamic Religious Education Curriculum in SMA IT Abu Bakar Yogyakarta - Fajar Fauzi Raharjo; Dedi Setiawan; Khodijah Khodijah; Triyono Triyono; Indra Prajoko (Journal of Research in Islamic Education, 2021)
This study aims to describe the curriculum development of Islamic Religious Education at SMA (Senior High School) IT (Integrated Islam) Abu Bakar Yogyakarta. Islamic Religious Education curriculum in non-madrasah schools needs to be developed in order to be able to answer the challenges. This research was conducted with a bibiliographic study and interviews. The results of this study found that the curriculum development of the Islamic Religious Education (PAI) at SMA IT Abu Bakar Yogyakarta integrated three educational environments (school, family and community), as well as science with Islamic teachings (specifically the version of Manhaj Tarbiyah Islam). Despite using KTSP curriculum, it still refers to the PAI curriculum of the Integrated Islamic Schools Network (JSIT), and is based on the teachings of Manhaj Tarbiyah. This is reflected in the curriculum material component, for example, which contains muwāshafat/ kifāyah tarbawiyyah, and also as in the component method that uses the exemplary approach.